Characterization of agroecological producers in the Pampas ecoregion of Argentina - O'Connor, Tomás; García, Germán O.; Cabral, Victoria N.; Isacch, Juan P. (Agrociencia Uruguay, 2022)
Agroecology is being developed in the Pampas region in Argentina as a response to the strong negative environmental and socioeconomic consequences of the conventional productive model. Thus, arises the need to characterize the producers who practice agroecology. A virtual survey was carried out obtaining a total of 103 accepted forms. Differences between intensive and extensive productions were analyzed using Fisher's test. According to the present study, in the Pampas region, agroecology has been developed mainly by people between 31 and 45 years old identified with both the male and female gender. They have diversified productions and they commercialize them mainly directly in their establishments. The majority have a close family that have worked the land, although there is also a 33% without such ties, who could be classed as what recently became known as neo-rurality movements. The extensive productions were differentiated from the intensive ones in the form of obtaining the land, the main production, the mode of commercialization, and the currents they identify with (i.e. biodynamic, natural agriculture).